The Influence of Location, Price, and Environmental Comfort on Customer Satisfaction at Warkop Aja in Gresik Regency - Mohammad Alan Wildani Thariq; Adiba Fuad Syamlan; Rachmad Ilham (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to analyze the influence of location, price, and environmental comfort on customer satisfaction at Warkop Aja, Gresik Regency. Customer satisfaction is a key factor in creating loyalty and improving customer retention, especially in the highly competitive culinary industry. A strategic location, affordable prices, and environmental comfort have been shown to significantly affect customer experiences in various business types. This study uses a quantitative explanatory approach with a survey method, where data were collected through a questionnaire distributed to 250 customers of Warkop Aja using a Likert scale of 1–5. Data analysis was performed using multiple linear regression to test the influence of each factor on customer satisfaction. The results show that location (path coefficient = 0.321), price (path coefficient = 0.289), and environmental comfort (path coefficient = 0.425) all have a significant impact on customer satisfaction, with p-values less than 0.05. This study concludes that the combination of these factors positively influences customer satisfaction at Warkop Aja, and therefore, coffee shop owners need to pay attention to these three aspects when planning their business strategies. This research also contributes to the development of customer satisfaction theory in the context of local culinary businesses, specifically in coffee shops in regional areas.